Acoustics of Classrooms in Primary Schools – Results of the Reverberation Time and the Speech Transmission Index Assessments in Selected Buildings - MIKULSKI, Witold; RADOSZ, Jan (Archives of Acoustics, 2011)
The article presents results of our own research regarding acoustic propertiesof 110 classrooms in five typical primary schools in Warsaw. The target of the research was to assess the classrooms using established criteria. These criteria include the reverberation time and the speech transmission index. The research has shown a large diversity of acoustic properties of classrooms within each of the schools and between the schools, resulting from the classroom equipment and the school building construction. In addition, the assessment has indicated that classrooms in schools researched do not meet the established acoustic criteria (reverberation time and speech transmission index). Because the classroom equipment is different for younger forms (integrated teaching) and for older forms (subject teaching), the results have been analyzed separately for rooms for younger forms (0–III) and for rooms for older forms (IV–VI). Synthetic results prove the advisability of such division. Correlation analysis has been conducted for the speech transmission indexSTI and reverberation time Tmf, as well as for the speech transmission index STI and the suggested reverberation time Twf defined in a similar manner as Tmf , but in a wider frequency range. The correlation between the speech transmission index STI and Twf is higher than that between the STI index and Tmf . The reverberation time Twf can therefore be used for a more precise assessment of acoustic properties of interiors with regard to verbal communication than $T_{mf}$. In addition, the paper presents estimated analysis results of the influence of selected classroom equipment (carpets) on its acoustic properties.